Administrative Courts System in the Republic of Uzbekistan: Stages of Formation, Legal Mechanisms, and the Essence of Reforms - Yangiboyev , Norquvvat; Xursanov , Mo‘min; Toshpo‘latov , Jasur (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
In modern jurisprudence, the system of administrative justice is recognized as one of the most important institutions ensuring balance in relations between public authorities and citizens. In a society based on the principles of the rule of law, effective judicial control over the activities of state authorities is essential. It is precisely the system of administrative courts that creates the institutional and procedural mechanisms for exercising such control.